Collaborative Professional Learning: Towards the Sustainability of Continuing Teacher Education for Quality Education - Palacios-Núñez, Madeleine Lourdes (2022)
The social and health crisis is a great challenge for education, as it requires a teacher prepared to "learn to learn" within a context of uncertainty. For this reason, the present study aims to carry out a descriptive and purposeful analysis of Collaborative Professional Learning (CPL), as a sustainable strategy and a driving force for continuous teacher training within the framework of quality education. For this, qualitative research was carried out by means of a semi-structured interview with eight international experts in education, which was conducted through the Atlas TI software version 7.5 in Spanish and subjected to thematic content analysis. The results revealed three emerging categories such as educational research supported by intergenerational collaboration, intra- and inter-institutional community resilience, and socio-emotional development needs for effective collaboration. The importance of Collaborative Professional Learning as a sustainable means for a higher qualification of the teacher in service is concluded, since it fosters their capacity for self-training, reflection and research, as well as learning to live together and learn to transform themselves and society.